Slice of heaven - Ang, Berlinda Hui Fang (2016)
This paper discusses the progress of my final year project, a short animation film named Slice of Heaven. In this paper, I will be discussing the main ideas behind this project, the learning progress and exploration of the software used to make this film, personal growth and a conclusion of this journey.